A new species and two new records of the moss-feeding lace bug genus Acalypta (Hemiptera, Heteroptera, Tingidae) from Hokkaido, northern Japan, with an illustrated key to the Japanese species of the genus - Jun Souma (ZooKeys)
In this study, three species of the moss-feeding lace bug genus Acalypta Westwood, 1840 (Hemiptera, Heteroptera, Tingidae, Tinginae, Acalyptaini) are reported mainly in Hokkaido, northern Japan. The first is Acalypta alutacea sp. nov. that inhabits mosses growing on the floors of deciduous broad-leaved forests. The second is Acalypta carinata (Panzer, 1806) that mainly inhabits mosses growing on marshlands and is recorded from Japan for the first time. The third is Acalypta sauteri Drake, 1942 that is widely distributed in three of the four main islands of Japan (Honshu, Shikoku, and Kyushu) and their surrounding islands, but is recorded from the remaining main island (Hokkaido) for the first time. The discovery of A. sauteri in Hokkaido also represents the northernmost record of this species. The following ten species of Acalypta are recognized in Japan: A. alutacea sp. nov., A. carinata, A. cooleyi Drake, 1917, A. gracilis (Fieber, 1844), A. hirashimai Takeya, 1962, A. marginata (Wolff, 1804), A. miyamotoi Takeya, 1962, A. pallidicoronata Souma, 2019, A. sauteri, and A. tsurugisana Tomokuni, 1972. An illustrated key for the identification of the ten species of this genus from Japan is also provided.